MFRP -Associated Retinopathy and Nanophthalmos in Two Irish Probands: A Case Report - Farrar, Gwyneth (My University, 2022)
The conjunction of nanophthalmos (NO) and retinitis pigmentosa (RP) provides challenges to effective clinical management while narrowing the genetic spectrum for targeted molecular diagnostics. This case study describes two not knowingly related adult cases of MFRP-associated retinopathy and nanophthalmos (MARN). Structural features including short axial lengths (mean 16.4 mm), steep keratometry (mean 49.98 D), adult-onset signs, and symptoms of retinal dystrophy and acquired disease (i.e., cataract, angle-closure glaucoma) were evident in both cases. Pathogenic variants in the MFRP gene impair both prenatal eye growth and childhood emmetropization while also leading to RPE/outer retinal degeneration in 75% of cases. We discuss the “small-eye” phenotype spectrum and associated defining characteristics, molecular mechanisms with particular focus on MFRP-associated NO with RP features (MARN), the spectrum of visual morbidities (e.g., extreme refractive error, amblyopia, cystoid macular lesions, early cataract) and the challenges of their treatment/surgical management.
Keywords: Retinitis pigmentosa; Nanophthalmos; MFRP gene; Inherited retinal degeneration; Ocular biometry